Efektivitas Penggunaan Media Sosial Tiktok Sebagai Media Promosi Demonsnia Parfum - Firna Is Tsaniyah; Uus Mohammad Darul Fadli (CV. ITTC INDONESIA, 2024)
TikTok is a social media site that is becoming popular quickly. Developing the TikTok social media platform as a strategic tool for promotional media for Demonsnia Perfume. Demonsnia is a perfume shop that was founded in November 2020 and is located on Jl Pasundan no. 46 West Adiarsa. This research aims to analyze the power of EWOM for Demonsnia Parfum products carried out via TikTok social media. In an effort to increase product visibility and appeal, a creative approach to TikTok content has been implemented by utilizing unique trends and styles that suit the intended target market. However, the lack of human resources in creating promotional content is an obstacle for these MSMEs. This research uses a qualitative method with an interpretive descriptive research type that uses in-depth interview techniques and uses source triangulation techniques as a data collection method. This research used four informants, divided into three main informants and one expert informant. The research results illustrate that EWOM TikTok, which is viewed from the three dimensions described by Goyette, et.al, is suitable for the content stage and plays a big role in convincing generation Z to make purchasing decisions on Demonsnia Parfum products via TikTok social media.